Spatiotemporal Dynamics of Chemovirotherapy on Immunogenic Tumours - Chakravarty, Koyel (Journal of Applied Nonlinear Dynamics, 2026)
Despite stupendous advancement of medical science, yet mankind gets perplexed when it comes to cancer. As yet cancer poses substantial threat to life as it is lethal in some cases due to its complexity and heterogeneity. With the objective of increasing the potency of cancer treatment, scientists are now focussing on combination therapy such as chemovirotherapy. In the current study, an updated and realistic mathematical model embracing different facets like uninfected tumour cells, infected tumour cells, free virus particles, chemotherapeutic agent, tumour specific immune cells and virus specific immune cells is advocated. In addition to mutual interactions between cells, diffusion phenomenon plays a vibrant role on account of their mobility. All these biological and physical processes are embodied in the novel mathematical model. Stability analysis corresponding to the temporal system along with its sub-models undergoing comparative study is performed. Suitable numerical methods are adopted for the model outcome followed by their exhaustive delineations. Spatial distributions are visualized using graphical manifestations. Sensitized parametric variation is illustrated pictorially. The study concludes that with proper management of model parameters so that cancerous tumours can be eradicated from the body using chemovirotherapy effectively.